2021
DOI: 10.1021/acs.analchem.1c02487
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Distribution of Acetaminophen and Its Metabolites in Rats, from the Whole-Body to Isolated Organ Levels, by Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging after On-Tissue Chemical Derivatization

Abstract: During drug development, detailed investigations of the pharmacokinetic profile of the drug are required to characterize its absorption, distribution, metabolism, and excretion properties. Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) is an established technique for studies of the distribution of drugs and their metabolites. It has advantages over autoradiography, which is conventionally used for distribution studies: it does not require the radiolabeling of drugs and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Accompanied with improvements in methods and techniques, MALDI MSI has been more and more widely used in the field of biomedical research such as disease diagnosis, 2,3 biomarker discovery, 4 and drug development. 5 Matrix selecting and matrix deposition are crucial steps for preparation of samples before MALDI MSI. Various matrixes, such as α-cyano-4-hydroxycinnamic acid (CCA) 6,7 and 2,5dihydroxybenzoic acid (DHB) 8,9 for analysis in positive mode; 9-aminoacridine (9-AA), 10,11 1,5-naphthalenediamine dihydrochloride (1,5-DANHCl), 12 N-(1-naphthyl)ethylenediamine dihydrochloride (NEDC), 13,14 and nitrogen-and sulfur-codoped carbon dots (N,S-co-doped CDs) 15 for analysis in negative mode; and 1,5-naphthalenediamine (1,5-DAN) 16,17 and 3-aminophthalhydrazide (Luminol) 18 for dual-polarity detection, have been used for MALDI MSI in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied with improvements in methods and techniques, MALDI MSI has been more and more widely used in the field of biomedical research such as disease diagnosis, 2,3 biomarker discovery, 4 and drug development. 5 Matrix selecting and matrix deposition are crucial steps for preparation of samples before MALDI MSI. Various matrixes, such as α-cyano-4-hydroxycinnamic acid (CCA) 6,7 and 2,5dihydroxybenzoic acid (DHB) 8,9 for analysis in positive mode; 9-aminoacridine (9-AA), 10,11 1,5-naphthalenediamine dihydrochloride (1,5-DANHCl), 12 N-(1-naphthyl)ethylenediamine dihydrochloride (NEDC), 13,14 and nitrogen-and sulfur-codoped carbon dots (N,S-co-doped CDs) 15 for analysis in negative mode; and 1,5-naphthalenediamine (1,5-DAN) 16,17 and 3-aminophthalhydrazide (Luminol) 18 for dual-polarity detection, have been used for MALDI MSI in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI), introduced by Caprioli et al in 1997, is a label-free method which allows in situ localizing of a wide range of biomolecules simultaneously with high sensitivity and molecular specificity from a tissue section in a single run. Accompanied with improvements in methods and techniques, MALDI MSI has been more and more widely used in the field of biomedical research such as disease diagnosis, , biomarker discovery, and drug development …”
Section: Introductionmentioning
confidence: 99%
“…Following this early innovative study, sensitivity was improved for oxidative metabolites when using MALDI-MSI on the whole-body section of rats. However, this was at the expenditure of spatial resolution since that was only at 400 μm pixel size. , While this may suggest that the rat may be ideal for MSI analysis of drug metabolism after an APAP overdose, much higher APAP doses are needed to induce toxic effects, and this would have limited clinical relevance since it has been shown that the pathophysiology of APAP hepatotoxicity in the rat is distinct from that of humans and thus the rat is not a clinically relevant model for studying APAP hepatotoxicity . To circumvent these issues with MALDI-MSI for analysis of APAP metabolism, we now show that the label and matrix-free DESI-MSI technique allows us to spatially map changes in APAP metabolism in the liver of the clinically relevant C57BL/6J murine model , after an APAP overdose.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Furthermore, the application of the MALDI matrices may also disturb the spatial localization of small molecules. 37,38 Several studies have applied MALDI-MSI to study the spatial distribution of APAP metabolism in mouse liver sections 39 as well as liver 40 or whole-body sections 41 from rats. However, no liver zonation was evident for APAP and its nonoxidative metabolites using the technique, which was unable to detect oxidative metabolites except APAP-GSH.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation